Market interdependence and volatility transmission among major crops - Gardebroek, Cornelis; Hernandez, Manuel A.; Robles, Miguel (International Food Policy Research Institute, 2014)
This paper provides a comprehensive analysis of the dynamics of volatility between the corn, wheat, and soybean markets in the United States. Volatility interactions across markets, if they exist, may lower the effectiveness of diversification strategies to mitigate price risks and should be taken into account when analyzing the pricing behavior of different agricultural commodities. We follow a Multivariate Generalized Autoregressive Conditional Heteroskedasticity (MGARCH) approach to evaluate the level of interdependence and volatility transmission across these major crops on a daily, weekly, and monthly basis.